+0

0
302
1

Guest Feb 14, 2017
Sort:

#1
+81072
0

cot^2(75°)

Note.....  csc^2(75°)   =  1 + cot^2(75°)      →  csc^2(75°)  - 1  = cot^2(75°)

sin(75°) = sin(30 + 45)  =  sin30cos45 + sin45cos30  =

(1/2) * sqrt(2)/2  + sqrt (2)/2  * sqrt (3)/2  =

sqrt (2) / 4  +  sqrt (6) / 4

sin^2(75°)  =  [sqrt (2) / 4  +  sqrt (6) / 4] =  2/16 + 2sqrt(12)/16 + 6/16  =

1/2  + sqrt(12)/8   =  (1/2   + 2sqrt(3) / 8 )  =  1/2 + sqrt(3)/4   =  [2 + sqrt(3)] / 4

1 / sin^2(75°) =    1 /  [ (2 + sqrt(3) ) / 4]  =       4 /  [ 2 + sqrt(3)] =

[4 * (2 - sqrt(3)) ] /  (  2 + sqrt(3) *  (2 - sqrt(3) ]  =

[4 * (2 - sqrt(3)) ]  / [ 4 - 3 ]  =

8 - 4sqrt (3)    = csc^2(75°)

csc^2(75°)  - 1  = cot^2(75°)

8 - 4sqrt (3) - 1  = cot^2(75°)

7 - 4sqrt (3)   = cot^2(75°)

CPhill  Feb 14, 2017

### 25 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details